Safety and feasibility evaluation of a novel robotic surgical system in gynecological surgery application - Yuanbo Tao; Jun Wang; ShiChao Han; Jing Na; Ya Li (Intelligent Surgery)
Objective: The study explores the safety, feasibility, and clinical application value of a novel robotic surgical system which is the Endoscopic Surgical Robot MT1000 (Shanghai MicroPort Medbot Co., Ltd., Shanghai, China) in gynecological surgeries. It aims to preliminarily establish a standardized process for the application of the novel robotic surgical system in gynecological procedures and analyze the learning curve associated with the docking technology of the novel robotic surgical system. Methods: This study conducts a retrospective analysis of the clinical data and recent outcomes of 82 patients who underwent the novel robotic-assisted laparoscopic gynecological surgeries by using the Endoscopic Surgical Robot MT1000 at the Gynecology Department of Dalian Medical University Second Affiliated Hospital from September 2022 to December 2023. It also compares the basic data and perioperative indicators of these patients with those of 82 patients who received da Vinci Si robotic-assisted laparoscopic gynecological surgeries during the same period. The cumulative summation (CUSUM) method is employed to analyze the learning curve associated with the docking technology of the novel robotic surgical system. Results: In this study, all 82 cases of the novel robotic surgery were successfully completed without any conversions to open surgery. The average surgical time was (134.15 ​± ​82.44) min, the average intraoperative blood loss was (29.16 ​± ​29.35) mL, the average time for postoperative bowel motility recovery was (27.0 ​± ​11.5) h, and the average hospital stay after surgery was (3.1 ​± ​1.3) d. There were no statistically significant differences (P ​> ​0.05) in surgical time, the difference in hemoglobin levels before and after surgery, the time of first flatus after surgery, the duration of indwelling catheter, the duration of indwelling drainage tube, and drainage volume at 48 and 72 ​h postoperatively between the two groups. However, there were statistically significant differences in intraoperative blood loss and length of stay after surgery (P ​< ​0.05). The CUSUM learning curve analysis indicated that the surgical team in the operating room became proficient in the docking technology of the novel robotic surgical system by the 34th case, while the bedside assistant mastered it by the 32nd case, achieving overall proficiency by the 33rd case. Conclusion: The novel surgical robot MT1000 is safe and feasible for application in the field of gynecology, demonstrating clinical applicability comparable to the da Vinci Si robotic system. Establishing standardized procedures can reduce preoperative preparation time and shorten the learning curve for the docking technology of the novel robotic surgical system. There is significant potential for the application of the novel robotic surgical system in China.